Numerical Simulation of Seepage-Heat-Solid Coupling of Gas Seepage in Prepumped Boreholes under Electrothermal High Temperature Field - Xionggang Xie; Jin Yang; XiangYing Luo; Jianjun Ren (Geofluids)
In order to verify the law of coal bed gas desorption and permeability under electrothermal high-temperature field, by establishing the mathematical model of gas seepage-heat-solid coupling, and taking gas drainage working face in Guizhou as an engineering example, the characteristics of the high-temperature field of coal under different heating hole temperatures are simulated. The COMSOL software is used to simulate the high-temperature field characteristics, thermal damage, and permeability of coal under different heating hole temperatures. The numerical simulation results show the following:(1) the influence trend of a high-temperature field on coal thermal damage and permeability is consistent, when the heating temperature is higher than 600°C, the thermal damage and permeability of coal seam change suddenly and increase with the increase of temperature. (2) When the temperature of a heating hole is 200-800°C, the gas permeability in the damaged area increases with the increase of temperature. When the heating temperature is greater than 600°C, the radial and axial permeability around the heating hole will increase. (3) Compared with the experimental data obtained by the existing researchers, the simulation results of coal permeability under the electric heating high-temperature field have a high consistency with the experimental results of Junrong and others.